Reading Literacy in Higher Education: Academic and Demographic Differences - Agus Jayadi,; Rila Hardiansyah,; Ahmad Muslim,; M Rasyid Ridlo,; Zulfakar,; Muhammad Iqbal, (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study investigated the relationship between reading literacy and academic characteristics among university students at the Faculty of Education and Psychology, Universitas Pendidikan Mandalika. Using a quantitative approach with a cross-sectional survey design, data were collected from 185 students across four study programs through a timed reading literacy test based on Bloom's taxonomy, comprising 10 items at cognitive levels C2 through C5. Chi-square analysis was employed to examine the association between reading literacy categories (Very Poor, Poor, Fair, Good, Very Good) and demographic variables. Results revealed significant associations between reading literacy and study program (χ² = 25.755, p = .012), gender (χ² = 12.861, p = .012), and academic semester (χ² = 26.786, p = .008). However, no significant relationship was found with GPA (χ² = 13.288, p = .102), school origin (χ² = 2.799, p = .592), or high school major (χ² = 12.506, p = .130). The majority of students (64.3%) demonstrated good to very good reading literacy, with a mean score of 77.44 (SD = 22.02). These findings suggest that institutional and demographic factors play important roles in shaping students' reading literacy competencies, while prior academic achievement may not be a reliable predictor of reading literacy performance in higher education contexts. Keywords: reading literacy, chi-square analysis, academic characteristics, university students. Abstrak: Penelitian ini bertujuan untuk mengkaji hubungan antara literasi membaca dengan karakteristik akademik mahasiswa di Fakultas Ilmu Pendidikan dan Psikologi, Universitas Pendidikan Mandalika. Menggunakan pendekatan kuantitatif dengan desain survei cross-sectional, data dikumpulkan dari 185 mahasiswa yang berasal dari empat program studi melalui tes literasi membaca terbatas waktu berdasarkan taksonomi Bloom, terdiri dari 10 butir soal pada level kognitif C2 hingga C5. Analisis chi-square digunakan untuk menguji hubungan antara kategori literasi membaca (Sangat Kurang, Kurang, Cukup, Baik, Sangat Baik) dengan variabel demografis. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara literasi membaca dengan program studi (χ² = 25,755; p = 0,012), jenis kelamin (χ² = 12,861; p = 0,012), dan semester akademik (χ² = 26,786; p = 0,008). Namun, tidak ditemukan hubungan yang signifikan dengan IPK (χ² = 13,288; p = 0,102), asal sekolah (χ² = 2,799; p = 0,592), atau jurusan di sekolah asal (χ² = 12,506; p = 0,130). Sebagian besar mahasiswa (64,3%) menunjukkan literasi membaca yang baik hingga sangat baik, dengan skor rata-rata 77,44 (SD = 22,02). Temuan ini mengindikasikan bahwa faktor institusional dan demografis memainkan peran penting dalam membentuk kompetensi literasi membaca mahasiswa, sementara prestasi akademik sebelumnya mungkin bukan prediktor yang andal untuk kinerja literasi membaca di konteks pendidikan tinggi. Kata Kunci: literasi membaca, analisis chi-square, karakteristik akademik, mahasiswa.